Marketing Communication Strategies of AA Collection Boutique to Boost Sales in Luwuk Subdistrict, Banggai Regency - Salsa Fadillah Sattu; Ken Amasita Saadjad; Kurniasari Khairunnisa (Jogjakarta Communication Conference (JCC), 2026)
The growing development of inicreasingly competitive local boutiques in the digital age requires business owners to implement effective marketing communication strategies. One such business is Aa Collection Boutique in Luwuk Subdistrict, Banggai Regency, which operates in the fashion industry. Therefore, this study aims to examine the marketing communication strategies employed by Aa Collection Boutique to increase sales in Luwuk Subdistrict, Banggai Regency. The method used in this study is a qualitative descriptive approach, employing data collection techniques such as observation, interviews, and documentation. Data were obtained through primary and secondary sources. The results indicate that Aa Collection Boutique’s marketing communication in Luwuk Subdistrict utilizes advertising, social media platforms (Facebook, WhatsApp, Instagram, and TikTok), sales promotions, and word-of-mouth marketing.